Outcomes With Surgery vs Functional Bracing for Patients With Closed, Displaced Humeral Shaft Fractures and the Need for Secondary Surgery: A Prespecified Secondary Analysis of the FISH Randomized Clinical Trial - Rämö, Lasse; Paavola, Mika; Sumrein, Bakir O; Lepola, Vesa; Lähdeoja, Tuomas; Ranstam, Jonas; Järvinen, Teppo L N; Taimela, Simo (JAMA surgery, 2021)
Existing evidence indicates that surgery fails to provide superior functional outcome over nonoperative care in patients with a closed humeral shaft fracture. However, up to one-third of patients treated nonoperatively may require secondary surgery. To compare the 2-year outcomes of patients who required secondary surgery with the outcomes of patients with successful initial treatment. This 2-year follow-up of the Finnish Shaft of the Humerus (FISH) randomized clinical trial comparing surgery with nonoperative treatment (functional brace) was completed in January 2020. Enrollment in the original trial was between November 2012 and January 2018 at 2 university hospital trauma centers in Finland. A total of 321 adult patients with closed, displaced humeral shaft fracture were assessed for eligibility. After excluding patients with cognitive disabilities, multimorbidity, or multiple trauma and those refusing randomization, 82 patients were randomized. Interventions were surgery with plate fixation (n = 38; initial surgery group) or functional bracing (n = 44); the latter group was divided into the successful fracture healing group (n = 30; bracing group) and the secondary surgery group (n = 14) with fracture healing problems. The primary outcome was Disabilities of Arm, Shoulder and Hand (DASH) score at 2 years (range, 0 to 100 points; 0 denotes no disability, 100 extreme disability; minimal clinically important difference, 10 points). Of 82 randomized patients, 38 (46%) were female. The mean (SD) age was 48.9 (17.1) years. A total of 74 patients (90%) completed the 2-year follow-up. At 2 years, the mean DASH score was 6.8 (95% CI, 2.3 to 11.4) in the initial surgery group, 6.0 (95% CI, 1.0 to 11.0) in the bracing group, and 17.5 (95% CI, 10.5 to 24.5) in the secondary surgery group. The between-group difference was -10.7 points (95% CI, -19.1 to -2.3; P = .01) between the initial and secondary surgery groups and -11.5 points (95% CI, -20.1 to -2.9; P = .009) between the bracing group and secondary surgery group. Patients contemplating treatment for closed humeral shaft fracture should be informed that two-thirds of patients treated with functional bracing may heal successfully while one-third may experience fracture healing problems that require secondary surgery and lead to inferior functional outcomes 2 years after the injury. ClinicalTrials.gov Identifier: NCT01719887.